Students’ English Learning Experiences on Virtual Project-Based Learning Instruction - Raida Asfihana; Kisman Salija; Iskandar Iskandar; Idawati Garim (International Journal of Language Education, 2022)
Project-based learning is a learner-centered process that gives freedom to the students to design their own project works. Though numerous research results on the enactment of Project-Based Learning instruction have already been reported, only a limited number has reported its enactment in an online classroom situation. This present research, employed Interpretative Phenomenological Analysis (IPA), unpacks the students’ learning experience after being exposed to Virtual Project-Based Learning, henceforth Virtual PBL. The researchers administered in-depth interviews to eighteen students who came from two different classes in an Islamic Higher Education in Indonesia. Findings show that five major themes emerged from data collection and analysis; increase active participation and motivation, develop critical thinking skills, participate in collaborative group discussion, build peer and lecturer communication, and develop skills in using digital tools. This result contributes to the earlier studies dealing with students’ learning experience of Virtual PBL instruction. It also adds the pedagogical implications to the research related to Virtual PBL enactment in Islamic higher education setting.